Genetic variability of functional longevity in five rabbit lines. (22nd June 2020) - EL Nagar, A. G.; Sánchez, J. P.; Ragab, M.; Mínguez, C.; Baselga, M.
Abstract : The objectives of this study were to analyse the differences in the genetic determination of functional longevity in five Spanish lines of rabbits and to check how different systematic factors might affect this genetic determination. Four of the lines were maternal (lines A, V, H and LP), these lines were established selecting base generation animals according to different criteria, but in the subsequent generations all of them were selected for litter size at weaning. The other is the paternal line R, this line was constituted by selecting animals with an outstanding daily growth rate. The trait analysed, length of productive life, was the time in days between the date of the first positive pregnancy test and the date of culling or death of a doe. Four models extended from the Cox proportional hazard model were used to analyse data of each line separately and jointly. The complete model (Model 1) included the fixed effect of year-season (YS ) combination, positive palpation order (OPP), that is, reproductive cycle, physiological status of the doe (PS ) at service and number of kits born alive (NBA ) in each kindling as time-dependent factors. The inbreeding coefficient was fitted as a continuous covariate and the animal's additive genetic effect was also fitted to the model (Model 1). The other models were identical to Model 1 but excluding OPP (Model 2) or PS (Model 3) or NBA (Model 4), which were explored to assess the consequence on additive variance estimates of not correcting for these animal-dependent factors. Estimated effective heritabilities of longevity were 0.07 ± 0.03, 0.03 ± 0.02, 0.14 ± 0.09, 0.05 ± 0.04, 0.02 ± 0.01 and 0.04 ± 0.01 for lines A, V, H, LP, R and for the merged data set, respectively. Removing the PS from the model led to an increase in the estimated additive genetic variance in all lines (0.17 ± 0.05, 0.05 ± 0.03, 0.29 ± 0.19, 0.29 ± 0.20, 0.07 ± 0.04 and 0.05 ± 0.02 for lines A, V, H, LP, R and the merged data set, respectively). The highest hazard of death and/or culling was observed during the first two parities and decreased as the order of parity progressed. Does non-pregnant-non-lactating had the highest risk of death or culling. The does that had zero kits born alive incurred the highest risk, and this risk decreased as the NBA increased. In conclusion, the consideration of longevity as selection criterion for the studied rabbit lines is not recommended.